Mental and physical health consequences of police brutality toward Black community members in the United States - Rebecca L. Fix (Elsevier, 2021)
Objectives: The current study was the first preliminary examination of physical and mental health outcomes for late adolescents impacted by police killing members of the Black community. Study design: Cross-sectional online survey research. Methods: 429 college students completed surveys in September 2020. Physical and mental health specific to police killing members of the Black community and general physical and mental health were measured. Black Lives Matter activism, safety concerns due to police brutality, negative police experiences, and anti-racist behavior were also quantified. Results: More variance was explained by Black Lives Matter activism factors for models examining physical and mental health specific to the recent killings of Black citizens by police compared with models examining general physical and mental health. Conclusions: Prevention efforts in healthcare and educational contexts should include screenings and education for those involved in Black Lives Matter activism or who have negative experiences (or worries about such experiences) with police.